Study of Micro-hardness of High-Speed W9Mo4Co8 Steel Plates in Pendulum Grinding by Abrasive Wheel Periphery - Yakov Iosifovich Soler; Van Canh Nguyen (Journal of Engineering and Technological Sciences, 2017)
In cutting tool assembly, grinding is the most important technological step of the finishing treatment, largely determining the workmanship. An increase of micro-hardness after grinding relative to the original one indicates the dominant role of abrasive tool force impact on the ground surface. A decrease, in contrast, evidences a significant softening under the influence of heat source. This research based on nonparametric statistics to predict the effect of wheel characteristics with abrasives 25A, 92A/25A, 34A, 5A, EKE, 5NQ, TGX, 5SG and with graininess 46 (F46), 60 (F60), 80 with different porosities (structure numbers 6-12), and the expected measures of position and dispersion on the micro-hardness of the surface of a high-speed cutting plate (HSCP) made of W9Mo4Co8 steel. It was found that grinding this HSCP by wheels 5NQ46I6VS3, 5SG46K12VXP, 5SG60K12VXP, 5SG46I12VXP, 25AF46M12V5"“PO, 25AF46M12V5"“PO3, 25ÐF46M10V5"“PO, 25AF46M10V5"“PO3, 25AF46K10V5"“PO3, 25AF60M10V5"“PO3, 25AF46L10V5"“KF35, EKE46K3V, 92A/25AF46L6V20 occurred without surface softening for 50% of the details from the operating batch.